2006
DOI: 10.1093/molehr/gal041
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase expression in endometriotic tissues and cell cultures of patients with endometriosis

Abstract: Cytochrome P-450 aromatase is responsible for catalysing the conversion of androstendione into estrone, so its expression in endometriotic tissue could contribute to the development of endometriosis. The aims of this study were, on the one hand, to determine the presence of aromatase in eutopic and ectopic endometrium, healthy peritoneum, myometrium and leiomyomas from patients with (n = 61) and without endometriosis (n = 12) and, on the other hand, to determine the effect of peritoneal fluid (PF), interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 33 publications
3
60
1
3
Order By: Relevance
“…The reduced ferritin mRNA expression in macroscopically normal peritoneum from women with endometriosis suggests that iron overload may be limited to endometriotic lesions and not extend to normal peritoneum. Because peritoneal mRNA expression of aromatase was not affected by the presence or absence of endometriosis, it is also possible that the main activity of aromatase is restricted to endometriosis lesions (10), confirming previous research (11), showing undetectable aromatase in healthy peritoneum of women with (proximal to endometriotic lesions) and without endometriosis. Eutopic endometrial expression of aromatase was increased in women with endometriosis compared with that of controls, according to some (5,(12)(13)(14)(15) but not all investigators (11,(16)(17)(18).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…The reduced ferritin mRNA expression in macroscopically normal peritoneum from women with endometriosis suggests that iron overload may be limited to endometriotic lesions and not extend to normal peritoneum. Because peritoneal mRNA expression of aromatase was not affected by the presence or absence of endometriosis, it is also possible that the main activity of aromatase is restricted to endometriosis lesions (10), confirming previous research (11), showing undetectable aromatase in healthy peritoneum of women with (proximal to endometriotic lesions) and without endometriosis. Eutopic endometrial expression of aromatase was increased in women with endometriosis compared with that of controls, according to some (5,(12)(13)(14)(15) but not all investigators (11,(16)(17)(18).…”
supporting
confidence: 84%
“…Because peritoneal mRNA expression of aromatase was not affected by the presence or absence of endometriosis, it is also possible that the main activity of aromatase is restricted to endometriosis lesions (10), confirming previous research (11), showing undetectable aromatase in healthy peritoneum of women with (proximal to endometriotic lesions) and without endometriosis. Eutopic endometrial expression of aromatase was increased in women with endometriosis compared with that of controls, according to some (5,(12)(13)(14)(15) but not all investigators (11,(16)(17)(18). Increased peritoneal mRNA expression of TGF-b and IL-1b in women with endometriosis compared with controls, observed in our previous study (5,6), was not confirmed in this study, possibly because of a different sample set or more robust methods for analysis, like normalization on 4 housekeeping genes in the current study compared with 1 housekeeping gene in our previous study (5,6).…”
supporting
confidence: 84%
“…This is probably caused by the local biosynthesis of E and the stimulation of PGE 2 , which are associated with proliferation, migration, angiogenesis, apoptosis resistance, and even invasiveness in several human cell lines. We reported (14) that the addition of peritoneal fluid, TNF␣, and especially IL-6 stimulated the basal enzymatic activity observed in endometriotic stromal cells, which suggests that the local production of E in endometriosis may be stimulated by factors such as cytokines or prostanoids present in the peritoneal fluid of patients with endometriosis. Thus, the presence of aromatase and the consequent synthesis of E may promote the growth of endometriotic implants, and probably favor the formation of leiomyomas, which are more frequent in women with endometriosis (22,23).…”
Section: Discussionmentioning
confidence: 85%
“…Immunohistochemistry for P450 aromatase was described by Velasco et al (14). Briefly, tissue samples were fixed with 10% paraformaldehyde solution, paraffin-embedded, and cut into 8-m serial sections.…”
Section: Immunohistochemistry For P450 Aromatasementioning
confidence: 99%
See 1 more Smart Citation